Researching the World of Work: Strategies and Methods in Studying Industrial Relations - Montreuil, Sylvie (Relations industrielles / Industrial Relations, 1999)
This article reviews the book, "Researching the World of Work - Strategies and Methods in Studying Industrial Relations," edited by Keith Whitfield and George Strauss.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; R&D; Research; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z